Bridging Tradition and Innovation: A Farm-Level Study on the Adoption of Modern Agricultural Technologies in Arunachal Pradesh and Assam (International Journal of Scientific Research in Science and Technology, 2025)
This study investigates the adoption of modern agricultural technologies among farmers in the North Eastern states of Arunachal Pradesh and Assam. Utilizing a mixed-methods approach, the research combines quantitative data analysis with qualitative insights to understand the factors influencing technology adoption. The findings reveal a moderate level of adoption, influenced by variables such as landholding size, education level and access to extension services. Qualitative analysis highlights the roles of cultural practices, terrain challenges and institutional support in shaping adoption patterns. The study concludes with policy recommendations aimed at enhancing technology dissemination and adoption in the region.